The underlying challenges of coordination of chronic care across Europe. (September 2014) - Knai, Cécile; Nolte, Ellen; Conklin, A; Pedersen, JS; Brereton, L
An effective response to the rising burden of chronic disease requires a health system environment that is conducive to implementing structured, integrated approaches to chronic disease prevention and management. This study presents some of the reported factors hindering the successful implementation of chronic care approaches in six European healthcare systems and focuses on processes to address these. We conducted 42 semi-structured interviews with key informants in Austria, Denmark, France, Germany, The Netherlands and Spain, representing the decision-maker, payer, provider and/or patient perspective. Despite differences among the healthcare systems studied, a shared set of barriers emerged. These included: (i) a continued focus on complications management and a failure to integrate risk minimisation and disease prevention along the spectrum of care; (ii) care fragmentation acting as a barrier to better coordination; (iii) a mismatch between intent, at national level, to enhance coordination and integration, and ability at regional or local level to translate these ambitions into practice; and (iv) a lack of structures suitable to promote proactive engagement with patients in the management of their own condition. Findings suggest successful implementation of chronic care across Europe will require cross-disciplinary collaboration, raising the profile of general practitioners and nurses, designing care explicitly around the needs of the patient, and the political will to carry forward these chronic care measures.